From Age 4 to 8, Children Become Increasingly Aware About Normative Situations for Adults to Consume Alcohol. (11th December 2019) - Voogt, Carmen; Smit, Koen; Kleinjan, Marloes; Otten, Roy; Scheffers, Tessa; Kuntsche, Emmanuel
Abstract: Aims: Limited cross-sectional studies have indicated that young children have some knowledge of the type of situations in which adults usually consume alcohol. However, it is unclear when and how this knowledge develops over time. This study tests the hypothesis that between the ages of 4 and 8, children become more knowledgeable about common drinking situations (e.g. 'partying') and uncommon situations (e.g. 'driving'). Methods: Data of two independent samples were used: a cross-sectional study (parents) and a three-wave longitudinal study (children). Parents and children were recruited via a convenience and random sampling strategy, respectively. To identify common, ambivalent, and uncommon drinking situations, parents ( N  = 158; 47% men) completed an online survey in which they indicated how common it is that any adult would drink alcohol in the 18 situations of the Dutch electronic appropriate beverage (eABT). Children ( N  = 329; 48.9% boys) completed the Dutch eABT to assess their knowledge of situations in which adults usually consume alcohol. Results: General linear model repeated measures with post-hoc pairwise comparisons showed that parents' perceptions of common, ambivalent, and uncommon situations in which adults consume alcohol predicted the initial level and the change over time in children's knowledge of adults' alcohol use in these situations. Conclusions: Children aged 4–8 become increasingly knowledgeable about drinking norms in specific situations which implies that they know in what kind of situation alcohol consumption is a common human behavior. This knowledge may put them at risk for early alcohol initiation and frequent drinking later in life. Abstract : Young children can distinguish situations in which alcoholic beverage consumption is more ('partying') or less common ('driving'). From age 4 to 8, children become increasingly knowledgeable about drinking norms in specific situations. This knowledge may put them at risk for early alcohol initiation and frequent drinking later in life.